Early Restenosis of Sirolimus-eluting Stent: An Unusual Case of a Hyperthyroid Patient - Shabbir, Syeda Javeria (Cureus, 2019)
The presentation of atherosclerosis with concomitant hyperthyroidism is not uncommon. Hyperthyroidism predisposes to worse cardiovascular pathologies like systolic hypertension, atrial fibrillation, and hypercoagulability. Drug-eluting stents, on the other hand, have emerged as a miracle treatment choice for patients having atherogenic conditions. They have the highest success rates when it comes to minimizing in-stent restenosis (ISR) during short-term follow-up. There is scarce literature that assesses the correlation of multinodular goiter (MNG) to ISR, especially in Pakistan, and thus any probable association between the two is left untouched. We report a case of a 57-year-old female who is a known hyperthyroid with a massive MNG, presenting with worsening chest pain. She had undergone sirolimus-eluting stent (SES) implantation in left anterior descending artery (LAD) six months back. Cardiac catheterization confirmed restenosis of the SES in the LAD, along with the occlusion of left circumflex and right coronary artery, accompanied by grade I diastolic dysfunction and mild aortic regurgitation on echocardiography.